Interactions with the macrophages: An emerging targeted approach using novel drug delivery systems in respiratory diseases. (1st May 2019) - Mehta, Meenu; Deeksha,; Sharma, Neha; Vyas, Manish; Khurana, Navneet; Maurya, Pawan Kumar; Singh, Harjeet; Andreoli de Jesus, Terezinha Pinto; Dureja, Harish; Chellappan, Dinesh Kumar; Gupta, Gaurav; Wadhwa, Ridhima; et al.
Abstract: Macrophages are considered as the most flexible cells of the hematopoietic system that are distributed in the tissues to act against pathogens and foreign particles. Macrophages are essential in maintaining homeostatic tissue processes, repair and immunity. Also, play important role in cytokine secretion and signal transduction of the infection so as to develop acquired immunity. Accounting to their involvement in pathogenesis, macrophages present a therapeutic target for the treatment of inflammatory respiratory diseases. This review focuses on novel drug delivery systems (NDDS) including nanoparticles, liposomes, dendrimers, microspheres etc that can target alveolar macrophage associated with inflammation, intracellular infection and lung cancer. The physiochemical properties and functional moieties of the NDDS attributes to enhanced macrophage targeting and uptake. The NDDS are promising for sustained drug delivery, reduced therapeutic dose, improved patient compliance and reduce drug toxicity. Further, the review also discuss about modified NDDS for specificity to the target and molecular targeting via anti-microbial peptides, kinases, NRF-2 and phosphodiesterase. Highlights: Macrophages are well-known immune cells present in the airways. Macrophages essentially retain pulmonary homeostasis and anti-inflammatory function. Macrophages present a therapeutic target for the treatment of respiratory diseases. Novel drug delivery system are gaining attention to target airways macrophages. Vesicular drug delivery provides improved patient compliance with lesser side effects.